The Angel Strikes: The Sennacherib Narrative in 2 Kings 18–19 as a Background to Herod’s Death in Acts 12:20–23 - Boogaard, Rogier (Novum Testamentum, 2026)
One of the most striking judgment scenes in the book of Acts is the death of Herod as described in Acts 12:20-23. Research on this text has neglected Second Kings 19:35 as a possible allusion. In this text, Sennacherib’s army is struck down by an angel of the Lord. This description is highly similar to that of Herod’s death. The aim of this article is to show that 2 Kings 18-19 functions as a background to the death of Herod. There are several connections between these texts, both on a semantic and theological level. This allusion was recognizable to Luke’s audience.